A cohort study of 30 day mortality after NON-EMERGENCY surgery in a COVID-19 cold site. (December 2020) - Kasivisvanathan, Veeru; Lindsay, Jamie; Rakshani-Moghadam, Sara; Elhamshary, Ahmed; Kapriniotis, Konstantinos; Kazantzis, Georgios; Syed, Bilal; Hines, John; Bex, Axel; Ho, Daniel Heffernan; Hayward, Martin; Bhan, Chetan; et al.
Abstract: Background: Two million non-emergency surgeries are being cancelled globally every week due to the COVID-19 pandemic, which will have a major impact on patients and healthcare systems. Methods: During the peak of the pandemic in the United Kingdom, we set up a multicentre cancer network amongst 14 National Health Service institutions, performing urological, thoracic, gynaecological and general surgical urgent and cancer operations at a central COVID-19 cold site. This is a cohort study of 500 consecutive patients undergoing surgery in this network. The primary outcome was 30-day mortality from COVID-19. Secondary outcomes included all-cause mortality and post-operative complications at 30-days. Results: 500 patients underwent surgery with median age 62.5 (IQR 51–71). 65% were male, 60% had a known diagnosis of cancer and 61% of surgeries were considered complex or major. No patient died from COVID-19 at 30-days. 30-day all-cause mortality was 3/500 (1%). 10 (2%) patients were diagnosed with COVID-19, 4 (1%) with confirmed laboratory diagnosis and 6 (1%) with probable COVID-19. 33/500 (7%) of patients developed Clavien-Dindo grade 3 or higher complications, with 1/33 (3%) occurring in a patient with COVID-19. Conclusion: It is safe to continue cancer and urgent surgery during the COVID-19 pandemic with appropriate service reconfiguration. Highlights: Priority surgeries are being cancelled every week due to the COVID-19 pandemic. A multicentre surgical referral network was set up as part of an NHS England approach to continuing safe surgery The referral network consisted of 14 NHS trusts and surgery was performed at a single COVID-19 'cold site'. After 500 surgeries performed, there was a 0% 30-day mortality from COVID-19. It is safe to continue cancer and priority surgery during the COVID-19 pandemic with appropriate service reconfiguration.